2018
DOI: 10.1038/s41467-018-04369-4
|View full text |Cite
|
Sign up to set email alerts
|

The rice blast resistance gene Ptr encodes an atypical protein required for broad-spectrum disease resistance

Abstract: Plant resistance genes typically encode proteins with nucleotide binding site-leucine rich repeat (NLR) domains. Here we show that Ptr is an atypical resistance gene encoding a protein with four Armadillo repeats. Ptr is required for broad-spectrum blast resistance mediated by the NLR R gene Pi-ta and by the associated R gene Pi-ta2. Ptr is expressed constitutively and encodes two isoforms that are mainly localized in the cytoplasm. A two base pair deletion within the Ptr coding region in the fast neutron-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
171
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(179 citation statements)
references
References 41 publications
3
171
0
5
Order By: Relevance
“…In the reference genome of Nipponbare (NPB), six NLR genes ( Os04g52970 , Os04g53000 , Os04g53030 , Os04g53050 , Os04g53120 and Os04g53160 ) form a tandem‐repeat R ‐gene cluster in the LABR12 region. LABR27 is co‐localized with two cloned R genes, Pita (Bryan et al , ) and Ptr (Zhao et al , ), and a previously identified R locus (Kang et al , ). Among the 27 LABRs, 5 are co‐localized with previously mapped or cloned R genes, and the other 22 are new (Table , Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In the reference genome of Nipponbare (NPB), six NLR genes ( Os04g52970 , Os04g53000 , Os04g53030 , Os04g53050 , Os04g53120 and Os04g53160 ) form a tandem‐repeat R ‐gene cluster in the LABR12 region. LABR27 is co‐localized with two cloned R genes, Pita (Bryan et al , ) and Ptr (Zhao et al , ), and a previously identified R locus (Kang et al , ). Among the 27 LABRs, 5 are co‐localized with previously mapped or cloned R genes, and the other 22 are new (Table , Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The genetic markers linked or derived from the cloned R genes were developed to predict resistance function and to monitor the existence of each of the R genes [31][32][33][44][45][46][47][48][49][50][51][52]. Differential blast races were identified ( Table 2) and have been used to validate their predicted resistance efficacies.…”
Section: Effective Major R Genesmentioning
confidence: 99%
“…Further analysis of Katy revealed that there are three linked blast R genes, Pi-ta and Pi-ta2/Ptr genes near the centromere of rice chromosome 12. Pi-ta is a classical R gene with NBS-LRR [63] and Ptr, which is allelic to Pi-ta2, encodes a predicted protein with four armadillo repeats [52]. Ptr was shown to confer resistance to a wide range of blast races except for IE1k and help Pi-ta with unknown mechanisms [52].…”
Section: Resistance Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Discovering rice blast resistance ( R ) genes is the premise of disease resistance breeding. To date, over 100 rice blast R genes have been identified and 36 of them were cloned (Wang, Ebbole, & Wang, 2017; Zhao et al, 2018). All of these genes encode nucleotide‐binding leucine‐rich repeat (NLR) proteins, except Pid2 , pi21 and Ptr , which encode a β‐lectin receptor‐like kinase, a heavy metal transport/detoxification protein and an Armadillo (ARM) repeat protein, respectively (Chen et al, 2006; Fukuoka et al, 2009; Zhao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%